METHODS OF FINANCING AND PRICING OF DEVELOPMENT - DESIGN DEVELOPMENT OF AERONAUTICAL ENGINEERING DEFENSE - V. P. Panagushin (Real Economics Publishing House, 2015)
The evaluation of the cost of development - development (R & D) at the conclusion of the state contract is proposed to conduct an estimated price of the replacement steps of the current standard OCD OCD stages, which are adequate and include several stages. At each stage, the limit is determined by the estimated price of the ROC, while retail prices are determined by the following steps and stages of their amount. Upon completion of all stages of the ROC, it is converted indicative price stages and the ROC in the fixed-price into the cost to the planned profit.